ENTREPRENEURSHIP MENTORING FOR STUDENTS THROUGH VEGETABLE CULTIVATION AT AL HIKMAH ISLAMIC BOARDING SCHOOL, TUBAN - Rahman, Tatang Aulia; Mumtahanah, Nurotun (Journal of Community Engagement in Economics, 2024)
The potential human resources and natural resources of the Al-Hikmah Islamic boarding school which is located in an agricultural area, is an opportunity for the development of Islamic boarding schools in the agricultural sector. The Al Hikmah Islamic boarding school has quite a large area of ​​land, but it has not been developed optimally by the students, because the Al-Hikmah Islamic boarding school students' ability to manage agricultural land is still limited and they do not understand cultivation techniques well. The problem experienced by the students of the Al Hikmah Islamic boarding school is the lack of awareness about independent consumption of vegetables which they always buy from outside parties, even though they have expertise in cultivating them healthily without using chemicals. To achieve small steps towards change, the Al Hikmah Islamic Institute's Community Service Program (PPkM) tries to solve this problem through activities to create farmer independence by cultivating growing vegetables. Apart from training students to grow plants effectively and efficiently, this assistance is expected to be able to train the spirit of independence and entrepreneurial spirit considering that these vegetable plants are plants that have the potential to be sold on the market.